Taxes and Mergers in Sweden - Karl-Markus Modén (The Research Institute of Industrial Economics (IUI), 1989)
This paper studies the relative importance of tax incentives as merger motives in the Swedish industry during the period 1983-1987. Several econometric models are estimated and statistical tests performed. The tax-hypothesis is contrasted with an alternative hypothesis, suggested by Jensen, which explains mergers as a way for independent managers to increase their personal power. Neither hypothesis get any strong support in this study, the evidence is somewhat stronger in favor of Jensen's theory however.
Keywords: G34; M54; 330; Tax incentives; merger motives; manager independence